SIADH-associated hyponatremia in hospitalized COVID-19 patients: relationship with ınflammatory and stress response markers - Okan Özgökçe; Murat Alay (Intercontinental Journal of Internal Medicine, 2026)
Aims: Hyponatremia observed during the course of COVID-19 infection is closely associated with disease prognosis. The objective of this study is to determine the prevalence of Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH) in patients diagnosed with COVID-19 and to analyze the relationship between this condition and inflammatory markers and stress response parameters. Methods: The study included 50 patients hospitalized with a diagnosis of COVID-19 who were found to have hyponatremia (Na